"Radio Free Sweden": Satire, National Identity, and the Un-PC (Geo)Politics of Jonatan Spang. Issue 1 (2nd January 2021) - Saunders, Robert A.; Bruun, Hanne
ABSTRACT: Focusing on Danish comedian Jonatan Spang's spoof of the Nordic drama The Bridge via his news parody series Close to the Truth, this article examines how satire simultaneously embodies and performs geopolitics. Through a close reading of Spang's send-up of contemporary Swedish culture as "pc-totalitarianism", we interrogate the comedian's satirical intervention in bilateral cultural relations between Denmark and Sweden. Our approach begins with a critical assessment of Danish national identity vis-à-vis the Swedish "other", followed by a brief history of Danish political satire, before shifting to an empirical analysis of Spang's controversial Draman skit across four spatio-cultural scales of engagement. In the concluding section, we integrate the various flows of satirical stereotyping, national identity production (and contestation), and geopolitics embedded in Spang's "humoristic Marshall Plan" for Sweden. Here, our goal is to provide a multi-tiered assessment of how comedy informs everyday understandings of International Relations (IR) between culturally-proximate nations.